Consumption and Trade of Asian Water Monitor, Varanus salvator as Reliance on Wildlife for Livelihoods among Rural Communities in North Sumatra, Indonesia - Evy Arida; Arief Hidayat; Mulyadi Mulyadi; Noor Laina Maireda; Dadang Rahadian Subasli; Mumpuni Mumpuni (Journal of Tropical Ethnobiology, 2020)
The water monitor, Varanus salvator has been exploited for its skin to supply international demands for reptile leather, whereas meat, liver, and fat are consumed locally in some communities in North Sumatra. Demands for skin seems to be paralleled with meat consumption in this province for more than 25 years. We conducted direct interviews with hunters and collecting managers in five abattoirs in five towns in North Sumatra to obtain preliminary data on consumption and trade of Water monitor. Additionally, we explore the association between consumption, trade, and livelihood of rural communities. We found that lizards of all sizes were taken and processed in the abattoirs for skin and meat trade. Consumption of Water monitor meat in North Sumatra is partially driven by a cultural background and has been occurring probably longer than the skin trade for leather industry. We noted that meat of Water monitor also becomes an alternative protein source because of its lower price. In conclusions, benefits of Water monitor harvest are extended across levels of participants in the local trade, including hunters, collectors, and meat consumers. Meat consumption and skin trade are closely linked with one another in North Sumatra; nevertheless sustainability of the trade needs to be evaluated in the near future to predict demands and production capacity.